Transport, Economic Growth, and Deforestation in the Democratic Republic of Congo : A Spatial Analysis - Damania, Richard; Barra, Alvaro Federico; Burnouf, Mathilde; Russ, Jason Daniel (World Bank, Washington, DC, 2016)
The purpose of this study is to demonstrate several techniques which can be used to evaluate pathways to sustainable growth in the Democratic Republic of Congo (DRC) via infrastructure improvement. Decades of conflict and neglect have left the DRC’s transport infrastructure amongst the sparsest and most dilapidated in the world.